Investigação empírica dos desafios e oportunidades da construção volumétrica offsite no Brasil: um estudo baseado em survey - Monteiro, Liza Bruna Reis (Universidade Federal de São Carlos, 2026)
Industrialization in the construction sector aims to enhance efficiency, quality, productivity, and sustainability by adopting industrial production methods. Despite gradual progress in Brazil, the large-scale implementation of industrialized construction - particularly volumetric offsite construction - remains constrained by multiple technical, economic, cultural, logistical, and institutional barriers. This study investigates the main challenges faced by the Brazilian Construction Industry in adopting volumetric offsite construction and identifies viable strategies to overcome them. A Systematic Literature Review was conducted to identify and consolidate the principal challenges reported in the Brazilian context. These findings informed the development of a Likert-scale questionnaire, which was pilot-tested and subsequently administered to professionals across the construction supply chain via survey. The results were analyzed through the Relative Importance Index (RII), enabling the ranking and categorization of challenges. The findings indicate that the most critical challenge categories are Financial (RII = 0.830), Governmental and Regulatory (RII = 0.826), and Cultural and Market-related (RII = 0.804). The highest-ranked individual challenges (RII > 0.80) include the transportation of large-scale modules, cultural resistance, shortage of skilled labor and market experience, lack of tax neutrality, and slow structural and administrative reforms. Proposed strategies to address these barriers include fiscal incentives and specific credit lines, regulatory updates and streamlined licensing, and enhanced technical dissemination, pilot projects, and stakeholder training. The study contributes empirical evidence to support decision-making by public and private stakeholders. It provides strategic guidance to foster the broader adoption of volumetric offsite construction in Brazil, promoting a transition towards more efficient and sustainable construction models.
Empirical investigation of the challenges and opportunities for volumetric offsite construction in Brazil: a survey-based study
Keywords: Construção civil; Desafios; Industrialização; Offsite; Survey; Construction industry; Challenges; Industrialization; ENGENHARIAS::ENGENHARIA CIVIL; 9. Indústria, Inovação e Infraestrutura